Low-dose human menopausal gonadotrophin versus natural cycles in intrauterine insemination for subfertile couples with regular menstruation - Sichen Li; Yuxia He; Mingzhu Cao; Hanyan Liu; Jianqiao Liu (BMC, 2020)
Abstract Background Women with irregular menstruation should be considered to benefit from the ovarian stimulation. However, most literature did not separate ovulatory disorders from normal menstrual cycles. Our purpose was to assess the superiority of ovarian mild stimulation compared with the natural cycle in IUI for subfertile couples when the women with regular menstruation. Methods A retrospective study in a single medical center in which 2413 couples with 3573 IUI cycles were studied from 2013 to 2018. The results of IUI in natural cycles versus low-dose HMG induced cycles were analyzed. Results For young women (age < 35 years) with normal menstrual cycle, HMG induced ovulation combined with IUI can improve clinical pregnancy outcome (13.55% in two follicular induced cycles vs. 7.23% in natural cycles, p < 0.01); even if only one follicle was induced, the clinical pregnancy rate was increased to 10.32% (p < 0.01). When two growth follicles were induced in HMG cycles, a remarkable improvement of the live birthrate (10.28% vs. 5.91% in natural cycles, p < 0.05) was noted. Simultaneously, twin pregnancy rates were increased to 20.69% (p < 0.01). Twin pregnancies showed significantly increased risk of both ectopic pregnancy and preterm birth (p = 0.00 for both). For advanced women (age ≥ 35 years) with regular menstrual cycle, ovulation induction didn't improve clinical pregnancy and live birthrates, while age was the only relevant factor. Conclusions Combining HMG induced ovulation and IUI can improve pregnancy outcome in young women with normal menstrual cycles. 1-2 follicles with diameter ≥ 14 mm served as the purpose of ovulation induction. Further, both twin and ectopic pregnancy rate in HMG cycles with two growth follicles were significantly higher than those in natural cycles were. Therefore, doctors must evaluate the risk before making choices and inform the patients to achieve the best results. For advanced women with normal menstrual cycles, natural IUI cycles were optional.